The Rellationship of Mother Knowledge and Husband Support of Post Placenta Intra Uterine Device Utilization Mothers Giving Birth at Aji Batara Agung Dewa Sakti Samboja Hospital in 2023 - Kurniawati, Lestari; Rahmawati, Eli; Setyawati, Ernani; Hariyani, Faridah (East Asian Journal of Multidisciplinary Research, 2024)
Based on data on the number of births and data on family planning acceptors at Aji Batara Agung Dewa Sakti Samboja in 2023, there are only 16.7% maternity mothers who choose to use a post placental IUD . The low use of post-placental IUDs is associated with several factors, including maternal knowledge and husband's support. This research aim to know exists connection between Mother knowledge and husband's support for the use of post-placental IUD at Aji Batara Agung Dewa Sakti Samboja Regional Hospital. This type of research uses descriptive analytics with a cross sectional research design approach . The sample in this study consisted of 58 respondents using a purposive sampling technique . Data analysis used the Chi-Square statistical test and multiple logistic regression test. Data was collected using questionnaire for each variable.